2015
DOI: 10.1038/ncomms7903
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of imino-C-nucleoside analogues and other biologically active iminosugars

Abstract: Iminosugars have attracted increasing attention as chemical probes, chaperones and leads for drug discovery. Despite several clinical successes, their de novo synthesis remains a significant challenge that also limits their integration with modern high-throughput screening technologies. Herein, we describe a unique synthetic strategy that converts a wide range of acetaldehyde derivatives into iminosugars and imino-C-nucleoside analogues in two or three straightforward transformations. We also show that this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…A facile access to complex iminosugars and imino‐ C ‐nucleoside analogues was recently provided in excellent yield, diastereoselectivity and enantioselectivity via proline catalyzed one‐pot reaction of aliphatic aldehydes 10 with N ‐chlorosuccinimide and dioxanone 12 (Figure ) . Under these reaction conditions 10 is α‐chlorinated and the S ‐proline catalyzed aldol condensation with 12 occurs with dynamic kinetic resolution (DKR) of the chloroaldehyde 11 , resulting in the aldol 13 as a single isomer.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…A facile access to complex iminosugars and imino‐ C ‐nucleoside analogues was recently provided in excellent yield, diastereoselectivity and enantioselectivity via proline catalyzed one‐pot reaction of aliphatic aldehydes 10 with N ‐chlorosuccinimide and dioxanone 12 (Figure ) . Under these reaction conditions 10 is α‐chlorinated and the S ‐proline catalyzed aldol condensation with 12 occurs with dynamic kinetic resolution (DKR) of the chloroaldehyde 11 , resulting in the aldol 13 as a single isomer.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…Although iminosugars have been extensively studied and have already found clinical use, recent efforts in their chemical synthesis coupled with an increased understanding of their affinity and target selectivity have notably improved their advancement as drug candidates. Efficient syntheses and new methods that allow to master the chemical and stereochemical complexity required are under continuous improvement …”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…Although recent progress in their de novo preparation through the diversity oriented synthetic approach by elegant asymmetric organocatalyzed processes [38,39,40] have been reported, one of the best methods remains the addition of C -Nu to N -glycosylamines.…”
Section: Introductionmentioning
confidence: 99%
“…However, while several examples of N ‐ and O ‐armed alkynyl iminosugars have been published, only one example of a 1‐ C ‐propargyl compound has been reported to date in the piperidine series (i.e., 1‐ C ‐propargyl‐1‐deoxyimino‐ d ‐xylitol) . A few examples based on a pyrrolidine core have been obtained by organocatalysis or through addition to cyclic N,O‐acetals or to cyclic nitrones …”
Section: Introductionmentioning
confidence: 99%
“…However, while several examples of N-and O-armed alkynyl iminosugars have been published, only one example of a 1-Cpropargyl compound has been reported to date in the piperidine series (i.e., 1-C-propargyl-1-deoxyimino-D-xylitol). [9] A few examples based on a pyrrolidine core have been obtained by organocatalysis [10] or through addition to cyclic N,O-acetals [11] or to cyclic nitrones. [12] In our group, we have previously shown that a 1-C-(2propynyl)-1,4-imino-L-arabinitol derivative could be straightforwardly prepared through the addition of a propargylzinc rea- Figure 1.…”
Section: Introductionmentioning
confidence: 99%